How to nudge students toward healthier snacks? Consumer neuroscience insights on multisensory nudge interventions in university vending machines. - Chiara Casiraghi; Simone Chiarelli; Giuseppina Gifuni; Alessandro Fici; Marco Bilucaglia; Alessandra Cecilia Jacomuzzi; Valeria Micheletto; Margherita Zito; Vincenzo Russo (PLoS ONE, 2025)
Nudge has proven effective in promoting healthier eating, especially in academic environments. However, its application in vending machines has not been extensively studied yet, with existing studies focusing on choice and overlooking the emotional and cognitive responses to these interventions. Our research explored how visual and olfactory nudges (and a combination of both) can encourage healthier choices in university vending machines, and examined the related emotional and cognitive reactions, adopting a consumer neuroscience approach. It encompassed three distinct analysis levels: behavioral (snack choice), neurophysiological (emotional and cognitive reactions assessed through skin conductance and electroencephalography), and attentional (visual attention on snacks evaluated via eye-tracking). The findings revealed that while visual and olfactory nudges, when considered individually, were associated with an increased likelihood of making healthier choices, their combined effect was not significant. Skin conductance indicated that olfactory and combined nudge interventions induced relaxation, potentially promoting healthier choices. Electroencephalography results suggested a reduced motivational approach toward snacks when both nudges were combined. Eye-tracking indicated that individuals pay heightened attention to healthy snacks when positioned at eye level, however, this can also be affected by the nudge condition. Our findings suggest that implementing visual or olfactory nudges alone may promote healthier choices in vending machines, whereas combining them may lessen their impact, and corroborate the importance of positioning target products in locations where they are readily visible to consumers. These insights enhance our understanding of the emotional, cognitive, and attentional components behind nudge interventions and offer practical strategies for promoting healthier eating habits.